2019
DOI: 10.1007/s11356-019-04799-7
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb) in the tissues of Anatidae, Ardeidae, Sternidae and Laridae of the Northern Hemisphere: a review of environmental studies

Abstract: Due to the ability of birds to travel long distances in the air, the potential feeding area of each individual is much larger than that of typical terrestrial animals. This makes birds a convenient indicator of environmental lead (Pb) pollution over large areas, in particular areas of inland and coastal waters. The aim of this study was to assess the concentrations of Pb in various organs of water birds from a variety of locations. The focus was on ducks, geese and swans ( Anatidae ); he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Information on the concentration levels of these elements in terns is fragmentary. Only a few research studies focused on the tissues of Laridae as reported for lead contamination in the review of Korbecki et al ( 2019 ) or Hg by Zamani-Ahmadmahmoodi et al ( 2014 ), and no studies have been conducted on tissues of T. bergii , S. repressa and O. anaethetus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on the concentration levels of these elements in terns is fragmentary. Only a few research studies focused on the tissues of Laridae as reported for lead contamination in the review of Korbecki et al ( 2019 ) or Hg by Zamani-Ahmadmahmoodi et al ( 2014 ), and no studies have been conducted on tissues of T. bergii , S. repressa and O. anaethetus .…”
Section: Discussionmentioning
confidence: 99%
“…Among seabirds, terns have been the subject of different environmental studies showing that Laridae are excellent bioindicators of TEs pollution (Khademi et al, 2015 ; Kitowski et al, 2018 ; Korbecki et al, 2019 ; Michelutti et al, 2010 ; Zamani-Ahmadmahmoodi et al, 2014 ). However, these latter studies did not take into consideration all types of TEs nor all tern species.…”
Section: Introductionmentioning
confidence: 99%
“…5). Korbecki et al (2019) also reported the differences in metal levels (Pb) found in feathers depending on the studied area and species. In general, feathers have been reported as a potential non-invasive tool for metal biomonitoring in seabirds (Hernández-Moreno et al 2021).…”
Section: Concentration Of Metals/metalloid According To Sampling Areamentioning
confidence: 99%
“…Some of the most relevant chemicals included in biomonitoring studies are metals. The appearance of metals in different tissues of animals often has been linked to specific urban areas (Korbecki et al 2019 ). In fact, there is a need to carry out ecotoxicological studies to obtain data on specific species over a wider range.…”
Section: Introductionmentioning
confidence: 99%
“…It exists in a variety of organic and inorganic compounds with a multitude of additional uses in the manufacture of protective paints for iron, steel, explosives, and rodenticide [3]. There are several measures put in place lately to checkmate industrial activities that result in Pb poison, and as well to prevent the careless introduction of lead from other sources [4]. However, these measures brought about positive changes, lead is still ranked among the top two most dangerous environmental toxicants hampering the health of humans [2,5].…”
Section: Introductionmentioning
confidence: 99%